Panelové sídliště a trvalá udržitelnost - Ezechýlová, Kristýna (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Bakalářská práce se zaměřuje na panelové sídliště v České republice jako symbolu masového bydlení, analyzuje jeho vliv na město a zkoumá možnosti a výzvy spojené s jejich trvalou udržitelností v dnešní době. V analytické části se zabývá historickým vývojem panelových sídlišť jako celku, principy a modely trvalé udržitelnosti. V návrhové části jsou tyto prvky spojeny a použity na návrh revitalizace daného panelové sídliště.

The bachelor thesis focuses on the panel housing estates in the Czech Republic as a symbol of mass housing, analyzes their impact on the city, and explores the possibilities and challenges associated with their long-term sustainability in today's context. The analytical part examines the historical development of panel housing estates as a whole, the principles, and models of sustainability. In the design part, these elements are interconnected and utilized in a proposal for the revitalization of a specific panel housing estate.
Prefabricated Housing and Sustainability
Keywords: Panelový dům; panelové sídliště; urbanismus; udržitelnost; životní prostředí; revitalizace; kvalitní prostor; veřejný prostor; soukromý prostor; hierarchizace prostoru; Panel house; panel housing estate; urbanism; sustainability; environment; revitalization; quality space; public space; private space; spatial hierarchy